SASTRA HIJAU PENYELAMAT BUMI - Risa Yanuarti Sholihah, Utia Putri Utami, Venty Saskia Rohmalita (BASA Journal of Language & Literature, 2021)
Natural conditions are getting worse. Damage to nature is everywhere. The water is no longer clean, the air is dirty, and the environment is no longer green. Unfortunately, human awareness of the preservation of nature is low. In the name of modernization and development, humans take massive actions regardless of their impact on the environment. This habit is considered normal. Now, nature, which is the carrying capacity for human survival, has become a killing force. Two different views, namely anthropocentrism and ecocentrism, are presented in interpreting nature. Green literature is here to campaign for saving the earth. Green literature not only contains beauty, but also brings people to reflect on the greatness and piety of humans towards the environment. The movement to save the environment through green literature is increasingly being echoed. The idea raised in this article is in the form of a green literary literacy movement. Through the green literary literacy movement, the call to love and care for nature is echoed. A noble act in response to increasingly sad natural conditions.